Asas Pemisahan Horisontal Dalam Politik Hukum Pertanahan - Rahman, Muhammad Ghazali; Tista, Adwin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The principle of horisontal separated is a principle in national land law that has a philosophical meaning to maximize the function of land for people's lives in customary law regarding land, which makes the position of land in a privileged position, this is then adopted by the national land law as set forth in the Law. The Basic Agrarian Law Number 5 of 1960 which was formed by the policies of the executive body and/or together with the legislature relating to regulations on land tenure, ownership, use and utilization. This is called the Politics of Land Law which is contained in Article 3 Paragraph (3) of the 1945 Constitution. The concept of the principle of horisontal separated of the politics of national land law is quite influential based on a philosophy to maximize the function of land for people's lives. This research method is normative legal research, namely by conducting a literature study using two legal materials, namely primary legal materials and secondary legal materials, with a statutory approach and a conceptual approach. Based on these considerations, the urgency of the principle of horisontal separated in national land law is essentially in order to fulfill the principles of expediency and justice which are reflected in the objectives and legal principles in Pancasila, the 1945 Constitution, and the Basic Agrarian Law.